Design of micro-hydropower system for a stand alone rural village electrification - Song, A.H.B (Universiti Malaysia Sarawak, UNIMAS, 2010)
Micro-hydropower system is a system that used to produce electricity. Its main concept is transfer the kinetic energy of water flowing to electric energy by a generator. When water flows from a head, the water flowing contains kinetic and potential energy. Thus, when water flows knocked the turbine bucket, the turbine will rotate and turning the generator. Generator can produce electric energy through rotation of dynamo that will cut through electromagnetic field. These all mechanisms are the main features of a complete micro hydropower system. The main objective of this study is to identify the equations used to do calculation regarding the system and main output is the parameter such as size of nozzle and turbine that need to use to produce desired power output. A program is created using Matlab7 software that includes the combination of equations to do calculation on deciding size and parameter of components that will be used during installation of the system. There are also a few limitations in this study such as the flexibility of the equation used in program created, system efficiency and limitation of materials selection for designing penstock system which the thickness can be calculated in the program. Recommendations are given to make the entire process more accurate and some problem can be solved.